دور التسويق الالكتروني في تنمية الميزة التنافسية للوكالات السياحية دراسة ميدانية على وكالة الثوابت للسياحة و الأسفار ولاية الوادي - عبد الغني،هالة; بلقاسم، بالرمان; مسعود،محضية (university of eloued جامعة الوادي, 2024)
تهدف الدراسة إلى معرفة دور التسويق الإلكتروني السياحي والفندقي في تنمية الميزة التنافسية للوكالات السـياحية في ولايـة الـوادي وقـد تمـت الدراسـة علـى مسـتوى وكالة الثوابت للسياحة و الأسفار بولايـة الـوادي ، كمـا هـدفت الدراسـة إلى وضـع إطـار نظـري عـام يهـدف إلى إبـراز مفهـوم التسـويق الإلكـتروني السـياحي والفنـدقي والميزة التنافسية، بالإضـافة إلى التعـرف علـى عناصـر المـزيج التسـويقي الإلكـتروني السـياحي والفندقي. ولغرض تحقيـق أهـداف الدراسـة قمنا بزيارة ميدانية للوكالة محل الدراسة لعرض وتحليل واختبـار الفرضـيات وصولا إلى نتـائج مفيدة، وقـد توصـلت الدراسـة إلى أن المؤسسة السياحية محل الدراسة تولي أهمية بالغة للتسويق الإلكتروني، كما أن هناك استخدام مكثف للتسـويق الإلكـتروني بالمؤسسـة السـياحية محـل الدراسـة، وكـذا يمكـن القـول أن التسـويق الإلكتروني يساهم في تنمية الميزة التنافسية من خلال تفعيل تقنيات المزيج التسويقي الإلكتروني. The study aims to understand the role of electronic marketing in tourism and hospitality in developing the competitive advantage of travel agencies in the Wilaya of El Oued. The study was conducted at Thawabet Travel Agency in the Wilaya of El Oued. Additionally, the study aimed to provide a general theoretical framework to highlight the concept of electronic marketing in tourism and hospitality and competitive advantage, in addition to identifying the elements of the electronic marketing mix in tourism and hospitality. To achieve the study's objectives, we conducted a field visit to the agency under study to present, analyze, and test the hypotheses, leading to useful results. The study found that the tourism institution under study places great importance on electronic marketing, and there is intensive use of electronic marketing at the tourism institution under study. It can also be said that electronic marketing contributes to the development of competitive advantage through the activation of electronic marketing mix techniques.
مذكرة ماستر علوم تجارية
Keywords: تسويق الإلكتروني السياحي والفندقي، الميزة التنافسية ،تسويق سياحي، مزيج تسويقي إلكتروني سياحي. Electronic marketing in tourism and hospitality; competitive advantage; tourism marketing; electronic marketing mix in tourism